Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3389/fmicb.2015.00365
|View full text |Cite
|
Sign up to set email alerts
|

Distinct microbial populations are tightly linked to the profile of dissolved iron in the methanic sediments of the Helgoland mud area, North Sea

Abstract: Iron reduction in subseafloor sulfate-depleted and methane-rich marine sediments is currently a subject of interest in subsurface geomicrobiology. While iron reduction and microorganisms involved have been well studied in marine surface sediments, little is known about microorganisms responsible for iron reduction in deep methanic sediments. Here, we used quantitative PCR-based 16S rRNA gene copy numbers and pyrosequencing-based relative abundances of bacteria and archaea to investigate covariance between dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(108 citation statements)
references
References 78 publications
7
101
0
Order By: Relevance
“…However, organisms responsible for metal-dependent AOM were not identified in these studies. It was speculated that JS1 bacteria, methanogenic archaea, and Methanohalobium /ANME-3 could be responsible for iron-dependent AOM [138]. Other researchers speculated that either ANME-1 or Methanococcoides /ANME-3 together with a bacterial partner were responsible for manganese-dependent AOM [139].…”
Section: Respiration During Anaerobic Oxidation Of Methanementioning
confidence: 99%
“…However, organisms responsible for metal-dependent AOM were not identified in these studies. It was speculated that JS1 bacteria, methanogenic archaea, and Methanohalobium /ANME-3 could be responsible for iron-dependent AOM [138]. Other researchers speculated that either ANME-1 or Methanococcoides /ANME-3 together with a bacterial partner were responsible for manganese-dependent AOM [139].…”
Section: Respiration During Anaerobic Oxidation Of Methanementioning
confidence: 99%
“…These two samples were located in mine adit (HX01) and downstream (HX04). In comparison, FeOX2 (crystalline Fe(oxyhydr)oxides, mainly goethite and hematite) and FeMag (crystalline Fe(oxyhydr)oxides, mainly magnetite and maghemite) (Oni et al 2015) accounted for smaller portion of Fetot. FeCarb containing adsorbed Fe and Fe carbonates was most abundant in HX04 (69.9 ± 0.1 mg/g, downstream), HX01 (50.8 ± 0.4 mg/g, mine adit), and CS04 (40.1 ± 0.2 mg/g, contaminated soil) but was relatively lower in other samples.…”
Section: Sequential Fe Extractionmentioning
confidence: 98%
“…The concentrations of four Fe-extractable fractions did not demonstrate a clear site-specific pattern. Among the four Fe-extractable fractions, FeOX1, referring to amorphous and crystalline Fe (mainly ferrihydrite and lepidocrocite) (Oni et al 2015), was most abundant. FeOX1 exhibited relatively high concentrations (>80 mg/ g) in ten samples, but lower in HX01 (9.5 ± 0.9 mg/g) and HX04 (9.2 ± 0.1 mg/g).…”
Section: Sequential Fe Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the classic reduction scheme in marine sediment based on theoretical calculations of energy yields, iron reduction has been thought to be limited to anoxic sediments above the SMTZ and only methanogenesis is thought to occur below the SMTZ (e.g., Berner, 1981;Emerson and Hedges, 2006). A more recent study, however, has indicated that microbial Fe reduction of iron minerals in the methanogenesis zone below the SMTZ and the release of Fe 2+ into porewater are possible (Oni et al, 2015). Indeed, the dissolved Fe concentrations in porewater below the SMTZ at Sites U1343 and U1344 imply that dissimilatory iron reduction occurs below the SMTZ.…”
Section: Fe(iii) Reduction In Clay Minerals Below the Sulfate-methanementioning
confidence: 99%